The Role of Artificial Intelligence and its Applications in Commercial Companies - Abbas Ziad Kamel Al-Saadi, (International Journal of Law Research and Studies, 2026)
In the mid-1950s, the term "artificial intelligence" was first used at an artificial intelligence conference, and researchers and academics began their journey to address the topic of artificial intelligence, its definitions, characteristics, role, and impact on the management of commercial companies.With the beginning of 2012 the spread of artificial intelligence (AI) began at a relatively rapid pace with the increase, growth and gradual development of databases in some fields, especially scientific ones, and services related to technology, communication, shopping, business management and others.In recent years, the development of artificial intelligence technology has made great leaps, and the most prominent manifestation of this is “deep learning” technology, which is based on the development of artificial neural networks that mimic the way the human brain works, meaning that they are able to experiment, learn and develop themselves automatically without human intervention.Artificial intelligence, machine learning, and computing are expected to achieve a fundamental technological leap that is indispensable for maximizing benefits in the corporate and business sectors across various fields. Geoffrey Hinton, an artificial intelligence researcher at Google and the University of Toronto, believes that "machines will be as intelligent as humans within five years."This research addresses the role and impact of using "artificial intelligence" in managing commercial companies and marketing their products, by explaining the legal and applied basis for its use, and its application in companies fulfilling their obligations, and its impact on the legal and legislative regulation of commercial companies. The statement of the position of the European Economic Council - in addition to the fact that most national legislations do not allow for compensation for human beings in the management of the company, and for the money and damage that may befall the shareholders.
Keywords: Commercial Companies; Digital Transformation; Artificial Intelligence; Company Management; Corporate Governance